Tinjauan Penggerudian Laser: Kemajuan, Teknik Optimasi, dan Aplikasi - Nasution, Abdul Haris; Ginting, Armansyah (Rekayasa Material, Manufaktur dan Energi, 2025)
This review paper presents a comprehensive analysis of laser drilling technologies, focusing on recent advancements, optimization techniques, and industrial applications. Laser drilling has emerged as a crucial non-conventional machining process for creating precise micro-holes in various materials, including composites, metals, ceramics, and silicon. The paper examines multiple aspects of laser drilling processes, including different laser types (CO2, Nd:YAG, fiber, femtosecond), optimization methodologies, and parameter influences on output quality characteristics. Special attention is given to challenges in drilling complex materials like Glass Fiber Reinforced Polymer (GFRP) composites, titanium alloys, stainless steel, and ceramic matrix composites. The review highlights optimization approaches such as Response Surface Methodology (RSM), Multi-Objective Genetic Algorithm (MOGA), and various metaheuristic algorithms including grey wolf optimizer. The paper also explores emerging techniques like water-assisted laser drilling, vector laser drilling, and laser-layered scanning that address limitations in conventional processes. Environmental and sustainability aspects are discussed, with emphasis on energy efficiency and reduced material waste. This review aims to provide researchers and industry practitioners with a comprehensive understanding of current laser drilling technologies, while identifying future research directions toward more efficient, sustainable, and high-quality laser drilling processes